Applying picture walk and read aloud strategies with supporting audio activities to enhance vocabulary mastery of Elementary School Students at SD Negeri 200104 Padangsidimpuan - Aprida Irmayana; Nina Nurbaidah; Kamisah Kamisah; Azril Maulana; Fatimah Junita Nasution; Juni Sharah Lubis; Nia Rahmadani Hasibuan; Riski Tresya; Suci Rahmadini Harahap; Yolanda Vanesa Andrini (Community Empowerment Journal, 2026)
This community service program (PKM) aims to improve English vocabulary mastery among sixth-grade students at SD Negeri 200104 Padangsidimpuan. The program implemented "Picture Walk" and "Read Aloud" strategies, structured within a systematic instructional design. To optimize the learning environment, audio technology via speakers was utilized for educational songs during ice-breaking sessions. The study involved 30 students, focusing on vocabulary related to fruits, human anatomy, and days of the week. Results indicated that the integration of audio technology and visual-based reading strategies significantly improved student engagement and vocabulary retention, fulfilling the predefined instructional objectives.